ANALISA PENERAPAN CONTROL SELF ASSESSMENT SEBAGAI APLIKASI PENGENDALIAN INTERN PADA PT. ABC INSURANCE - Martias, Andi (Universitas Bina Sarana Informatika, 2016)
In order to meet the needs of the development of the internal auditing profession, one of the efforts is to hold the Control Self Assessment (CSA) to any existing processes in the unit. the unit in good company branch or head office. CSA is carried out for business purposes in a wider scale include profit maximization, repair the product or process, etc. Errors arising from the implementation could be negligence of the PIC related but also due to a lack of oversight double of the relevant parties. When the process is carried out a re-examination has been carried out, the error that occurred can be detected early and can be done endorsement or changes on the same day. This simple analysis using the percentage comparison between the results of the audit report to the regional level of risk that exist and conformity with CSA used to view the Internal Control Applications With the Approach CSA. Description and analysis that has been discussed previously, it can be concluded as follows : 1. Can be applied and useful to identify the risks that have been or will happen, 2. Internal auditors as fasiliasator very helpful in the process of applying. 3. Errors above apart due to negligence of the PIC related but also due to a lack of oversight double of the relevant parties. 4. Spread and the large number of control causing no bias control allows all tested by internal and external audits, thereby Control Self Assessmen into the solution. keywords: Internal auditing, Control self assessment, Dual control